East-central Florida pre-Columbian wood sculpture: Radiocarbon dating, wood identification and strontium isotope studies - Ostapkowicz, J; Schulting, R; Wheeler, R; Newsom, L; Brock, F; Bull, I; Snoeck, C (Elsevier, 2017)
A suite of scientific approaches are applied to four pre- Columbian wood sculptures from east-central Florida, comprising new radiocarbon determinations, wood identification and strontium isotope analysis. The dates for three large zoomorphic carvings recovered from the St. Johns River at Hontoon Island place them between ca. AD 1300 and 1600, suggesting that they belonged to a tradition of erecting largescale pine carvings spanning at least some centuries. Two of the carvings have strontium isotope signals consistent with the immediate vicinity of the site, while the third differs significantly. Baseline data for biologically available strontium from sampled modern trees indicates considerable isotopic variability over short distances, making it difficult to determine the source of the wood used for this third carving. The only anthropomorphic sculpture, recovered from the vicinity of Tomoka State Park, dates to a similar time period, ca. AD 1440-1620. Our study confirms the wood's previous identification as belonging to the genus Peltophorum, a tropical hardwood thought not to be native to Florida. Its strontium isotope value is consistent with its find location, but equally may be found over much of southern Florida, where perhaps the species grew in the past. The results clarify the chronology for a stylistically distinctive carving tradition, as well as raising questions concerning the exchange of organic materials over varying distances. Highlights • 14C results for four east-central Florida carvings (Hontoon Island; Tomoka State Park) range ca. AD 1300-1600, spanning the proto-historic/historic periods • 87Sr/86Sr results for two of the three Hontoon carvings are consistent with the immediate locale, while the third suggests a different provenance • Pinus sp. was used at Hontoon, while Peltophorum sp., currently not native to Florida, was used at Tomoka